Schistosomiasis mansoni in the municipality of Pedro de Toledo (São Paulo, Brazil) where the Biomphalaria tenagophila is the snail host: I - Prevalence in human population ( - Dias, L. C. S.; Kawazoe, U.; Glasser, C.; Hoshino-Shimizu, S.; Kanamura, H. Y.; Cordeiro, J. A.; Guarita, O. F.; Ishihata, G. J. (Revista do Instituto de Medicina Tropical de São Paulo, 1989)
Due to the scarce information about the epidemiological features of schistosomiasis in which the vector is Biomphalaria tenagophila, an investigation was carried in Pedro de Toledo in 1980 where such peculiarity is observed. Stool examinations (Kato-Katz method) were performed in 4,741 individuals (22.8% positive to Schistosoma mansoni eggs) of this 583 had previously received chemoterapy and 4,158 remainders, untreated. The schistosomiasis prevalence in those two groups where respectively 31.7% and 21.6%. Epidemiological investigation showed that 83.6% were autochthonous cases from the studied area: the autochthonous prevalence rate, and the intensity of infection in the untreated autochthonous cases were higher in males than in females; the intensity in the latter untreated group was low, 58.5 eggs/g feces (geometric mean). Moreover, according to the age groups the intensity of infections correlated well (r s = 0.745) with the prevalence rates. Schistosomiasis was verified to occur mostly during the leisure time and by the use of water streams for housework in rural zone. Only 0.4% out of 1,137 snails was positive for S. mansoni cercariae, apparently unchanged from the 1978 study when the human prevalence was 12.0%. The studied area presented differences and similarities in relation to the other Brazilian areas were the main intermediate host is B. glabrata.